PELAKSANAAN PERATURAN DAERAH NOMOR 1 TAHUN 2015 DALAM PENANGANAN GELANDANGAN DAN PENGEMIS DI KOTA DENPASAR - I Gede Krisna Agastya; Kadek Apriliani (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
The issuance of Regional Regulation Number 1 of 2015 concerning Public Order which regulates the homeless and beggars is an attempt by the Denpasar City government to create a safe and comfortable city for vacationing because Denpasar City is a world tourism destination and Denpasar City is a City of Culture. The problem examined in this thesis is how the implementation and the factors that influence the implementation of the Denpasar City Regulation Number 1 of 2015 in handling homeless and beggars in Denpasar City. The research method used is the empirical research method with the rule of law theory and the theory of effectiveness. The results of the research on the Implementation of Regional Regulation Number 1 of 2015 in Handling Homeless and Beggars in Denpasar City are not going well, there are still many homeless and begging activities in Denpasar City, so that it still disturbs public order. The government is still trying to deal with the social problems of homeless people and beggars by means of preventive efforts, repressive efforts, and rehabilitation efforts.